Official guidelines for homestay programmes in Malaysia / Muhammad Hanif Othman - Othman, Muhammad Hani (Universiti Teknologi MARA, Kedah, 2022)
The Malaysian Homestay Registration Guidelines were made public by the Ministry of Tourism so that communities and families may formally enrol their homestay programs. These regulations state that all sorts of communities and families with permanent dwellings in rural regions are welcome to participate in these homestay programs (Ramele et al., 2020). For a village to register as a homestay village, it must consist of more than 10 participating family houses as an additional requirement by the Ministry of Tourism, Arts and Culture (MOTAC). Figure 1 below outlines the details of the registration process for a homestay participant to register under MOTAC from the application until the homestay programme can be carried out. According to a discussion with Haji Basir Bin Wagiman, the chairman of Banghuris Homestay, people who are eager to designate their property as an official homestay through MOTAC may begin the registration process by sending the registration form to the ministry. Subsequently, several agencies such as MOTAC, the Ministry of Health Malaysia, and the Homestay Association in each state, including the existing Village Development and Security Committee (VDSC), will determine a date to inspect the host family house within a week after they submitted the application form. Over a one-month period, the host family shall receive a notice of whether their application to register their residence to become a homestay is accepted. If the participant fails the house inspection, they can reapply for inspection after improvements have been made. After passing the inspection process, the participant must attend the Homestay Basic Training, organised by the Institute for Rural Advancement (INFRA). Only upon successfully completing the training is the participant officially registered. The official logo, issued by the ministry, may be used by individuals who have been verified by MOTAC (Figure 2). Moreover, every three years, MOTAC will inspect each residence to ensure the host family is complying with the regulations. The official logo of the Malaysian Homestay Programme, issued by MOTAC, serves to identify the homestay providers. Figure 3 shows the official Malaysian Homestay Programme logo, which is usually placed at the main entrance of the operators’ residences. This logo placement is to differentiate between operators’ houses and other villagers’ houses.